The emergence and growth of dial-up internet service providers (ISPs) as a means of access to the internet in South Africa: a case study of M-Web and World Online - De Vos Belgraver, Cecilia Susan (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2003)
The desire amongst media scholars for the fulfilment of the ideal of a universally accessible public sphere by the media is such that virtually every new communications technology that has emerged over the past 1 ~O-odd years such as radio, television or the Internet has been welcomed with enthusiasm - by some - at the prospect of the newest communications innovation bringing about universal access to information. However, the history of communications media tells of the commercialisation of each new medium, from radio to television, and the imposition of barriers to access, based on cost. Access to communications media is open to those people who can afford to pay for them. 111e emergence of the Internet spawned renewed hoped that the public sphere ideal would be realised. 111is new technology seemed more powerful than anything that had come before it. The Internet offered the means whereby one could access a global repository of information, stored on a worldwide network of computer networks, and available 24 hours a day. With the Internet, it was also possible to communicate with people on the other side of the world within seconds, using electronic mail (e-mail). Here was a medium that permitted one to send text and pictures to colleagues and friends within a fraction of the time taken by traditional means such as fax, telephone or post. To enjoy the convenience of the Internet though, one had to have a means of access. In South Africa, access could be gained through a personal computer linked to the Internet either through a network in the workplace or an academic or research institution, or via a telephone link to an Internet Service Provider (ISP). What were the names of the first ISPs to emerge in South Africa? When did they emerge and how did they develop? Did the number of ISPs grow or decline? What do ISPs give access to, at what cost and to whom? Do they provide universal access to information? This study addresses these questions by examining South Africa's leading providers of home dial-up internet access, M-Web and World Online, and by exploring the histories of their emergence and development, within the context of current media trends of concentration, diversification and globalisation.
Keywords: Internet service providers -- South Africa; Internet service providers -- South Africa -- Case studies; M-Web; World Online